How to write a lot : a practical guide to productive academic writing - Silvia, Paul J., 1976- (2019)
"All academics need to write, and many struggle to finish their dissertations, articles, books, or grant proposals. Writing is hard work and can be difficult to wedge into a frenetic academic schedule. This revised and updated edition of Paul Silvia's popular guide provides practical, lighthearted advice to help academics overcome common barriers and become productive writers. Silvia's expert tips have been updated to apply to a wide variety of disciplines, and this edition has a new chapter devoted to grant and fellowship writing"--
Includes bibliographical references (pages 135-138) and index.
Keywords: English language -- Rhetoric; Academic writing; Writing; Research